Evaluasi Pembelajaran Menyimak di Kelas Tinggi - Fadya Safitri Rahman; Rizki Ramadhani; Windi Melisa; Juni Sahla Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Listening skills also influence students' writing skills. In every writing lesson, students need inspiration through information or stories they hear from teachers or other people. Therefore, listening skills are correlated with writing skills. Furthermore, the connection between listening skills and reading lies in the pronunciation of the sound of a word. Without listening, students cannot identify the sounds of words so they may not be able to read. The important role of evaluating language learning in elementary schools is to become the basis for decision making and policy making, measuring student achievement, evaluating the curriculum, accrediting schools, monitoring the use of public funds, improving educational materials and programs. Learning evaluation functions for development and accreditation. In conducting language learning evaluations in elementary schools, test and non-test techniques can be used. The purpose of assessing listening skills learning is to find out whether everything experienced by students in learning is in accordance with basic competencies, especially indicators. Learning evaluation is divided into four types of evaluation, namely, Formative Evaluation, Summative Evaluation, Diagnostic Evaluation and Placement Evaluation.